Analysis of viscous fluid flow in a pressure-swirl atomizer using large-eddy simulation. (April 2019) - Laurila, E.; Roenby, J.; Maakala, V.; Peltonen, P.; Kahila, H.; Vuorinen, V.
Highlights: Numerical investigation of a large-scale, asymmetric pressure-swirl atomizer. The simulations include inner nozzle flow and the onset of liquid film instability. Various nozzle operation modes revealed by a Reynolds number sweep. Liquid sheet types characterized for different Reynolds numbers. Rich physics include vortex core, Dean vortices, sheet flapping and breakup. Abstract: A computational fluid dynamics study is carried out on the inner nozzle flow and onset of liquid sheet instability in a large-scale pressure-swirl atomizer with asymmetric inflow configuration for high viscosity fluids. Large-eddy simulations (LES) of the two-phase flow indicate the unsteady flow character inside the nozzle and its influence on liquid sheet formation. A novel geometric volume-of-fluid (VOF) method by Roenby et al. (2016), termed isoAdvector, is applied for sharp interface capturing. We carry out a Reynolds number sweep (420 ≤ Re ≤ 5300) in order to investigate the link between the asymmetric inner nozzle flow and liquid sheet characteristics in laminar, transitional and fully turbulent conditions. Inside the nozzle, the numerical simulations reveal counter-rotating Dean vortices, flow impingement locations, and strong asymmetric flow features at all investigated Reynolds numbers. A helical, rotating gaseous core is observed when Re ≥ 1660. For laminar flow ( R e = 420 ), an S-shaped liquid film is observed, while the gas core presence at Re ≥ 1660 results in a hollow cone liquid sheet. For the intermediate value R e = 830, the numerical simulations indicate a liquid sheet of mixed type. Consequences of the inflow asymmetry and Reynolds number to the uniformity of the injected liquid mass distribution and liquid sheet instability are pointed out.